2022
DOI: 10.1111/ases.13057
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic vaporization of benign prostatic hyperplasia using a contact 980 nm diode laser under antithrombotic therapy: A prospective survey

Abstract: Introduction: To prospectively clarify whether endoscopic contact laser vaporization of the prostate (CVP) can be safely performed even in patients undergoing antithrombotic therapy. Methods: Fifty-five patients treated with CVP were enrolled. Patients were assigned to: (i) the antithrombotic therapy group (n = 21, 38%); or (ii) control group without antithrombotic therapy (n = 34, 62%). All patients in the antithrombotic therapy group continued all antithrombotic agents during the perioperative period and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(23 reference statements)
0
4
1
Order By: Relevance
“…Sanjo et al. reported that CVP can be performed safely and effectively in patients undergoing continuous antithrombotic therapy 12 . According to these studies, the results for operative time and complications were not significantly different from our results.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Sanjo et al. reported that CVP can be performed safely and effectively in patients undergoing continuous antithrombotic therapy 12 . According to these studies, the results for operative time and complications were not significantly different from our results.…”
Section: Discussioncontrasting
confidence: 70%
“…Therefore, in this study, we used three items as trifecta (operative time, operative efficacy, and complications). Previous studies investigated operative efficacy (calculated as the prostate volume divided by operative time) and initial experience reports were 0.61-1.0 cc/min, [10][11][12] with no difference in our study. In addition, previous clinical studies on TURP reported that operative efficacy (preoperative prostate volume divided by operative time) was approximately 0.85-1.0 cc/min and the operative resection efficacy (resection weight divided by operative time) was approximately 0.54-0.67 g/min.…”
Section: Discussionmentioning
confidence: 52%
“…20 Previous studies have documented a significant prevalence of dysuria and burning micturition. 21 The prevalence rates of dysuria and burning micturition in this study were 29% and 46%, respectively. In addition, a limited number of studies have documented elevated re-operation rates ranging from 8% to 33% and a persistent prevalence of stress urine incontinence at 9.1%, while we have found 11% stress incontinence.…”
Section: Discussionmentioning
confidence: 47%
“…CVP and other endoscopic laser vaporization procedures can be safely performed even in patients under antithrombotic therapy because of reduced bleeding compared with traditional transurethral surgery. 2,5,6 As patients undergoing surgery for BPH are aging, the number of patients receiving antithrombotic therapy has increased, and laser vaporization techniques have gained popularity as a treatment for BPH. 16,17 Among patients for whom laser vaporization of the prostate is considered, a certain number of patients have slightly elevated PSA levels but a low likelihood of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Laser vaporization of the prostate is associated with reduced bleeding compared with traditional transurethral surgery and is considered safe, even for patients under antithrombotic therapy. 2,5,6 Prostate cancer is the second most commonly diagnosed cancer in men. 7 Prostate-specific antigen (PSA) screening test is recommended for early detection of prostate cancer, particularly in elderly men.…”
Section: Introductionmentioning
confidence: 99%